Analytical model for measurement of through-thickness axisymmetric radial residual stress. (15th June 2022) - Liu, Huan; Deng, Lu; He, YuLong
Abstract: In this study, an analytical model is proposed to measure the through-thickness axisymmetric radial residual stress. Firstly, the rigorous analytical solution for the strain of a plate with a hole subjected to the through-thickness axisymmetric radial stress is found based on the general solution for a homogeneous isotropic elastic solid. It is assumed that the through-thickness axisymmetric radial residual stress can be expanded into the Maclaurin series. Then, the reverse procedure is proposed to determine the coefficients of the series by minimizing the predicted and measured surface radial strains with hole drilling. The proposed model is validated by finite element method (FEM) for a few typical distribution types. The influence of individual terms of the series on the surface radial strain is investigated, and the results show that the high order term results in a small strain value. The model is able to predict the residual stresses by peening as well as those with linear, bi-linear, quad-linear, and sinusoidal distributions. Moreover, a method to measure the resultant force and moment per unit hole circumference is proposed. Highlights: Analytical solution is derived for the axisymmetric problem of a plate with a hole. The reverse procedure is established for the prediction of the stress. The model is able to predict the residual stresses with different distribution types.